Beta 2 Adrenergic Receptor Selective Antagonist Enhances Mechanically Stimulated Bone Anabolism in Aged Mice. (27th December 2022) - E. Worton, Leah; Srinivasan, Sundar; Threet, DeWayne; Ausk, Brandon J.; Huber, Phillipe; Y. Kwon, Ronald; Bain, Steven D.; Gross, Ted S.; M. Gardiner, Edith
Abstract: The anabolic response of aged bone to skeletal loading is typically poor. Efforts to improve mechanotransduction in aged bone have met with limited success. This study investigated whether the bone response to direct skeletal loading is improved by reducing sympathetic suppression of osteoblastic bone formation via β2AR. To test this possibility, we treated aged wild‐type C57BL/6 mice with a selective β2AR antagonist, butaxamine (Butax), before each of nine bouts of cantilever bending of the right tibia. Midshaft periosteal bone formation was assessed by dynamic histomorphometry of loaded and contralateral tibias. Butax treatment did not alter osteoblast activity of contralateral tibias. Loading alone induced a modest but significant osteogenic response. However, when loading was combined with Butax pretreatment, the anabolic response was significantly elevated compared with loading preceded by saline injection. Subsequent studies in osteoblastic cultures revealed complex negative interactions between adrenergic and mechanically induced intracellular signaling. Activation of β2AR by treatment with the β1, β2‐agonist isoproterenol (ISO) before fluid flow exposure diminished mechanically stimulated ERK1/2 phosphorylation in primary bone cell outgrowth cultures and AKT phosphorylation in MC3T3‐E1 pre‐osteoblast cultures. Expression of mechanosensitive Fos and Ptgs2 genes was enhanced with ISO treatment and reduced with flow in both MC3T3‐E1 and primary cultures. Finally, co‐treatment of MC3T3‐E1 cells with Butax reversed these ISO effects, confirming a critical role for β2AR in these responses. In combination, these results demonstrate that selective inhibition of β2AR is sufficient to enhance the anabolic response of the aged skeleton to loading, potentially via direct effects upon osteoblasts. © 2022 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research. Abstract :